2019
DOI: 10.1039/c9sm01769k
|View full text |Cite
|
Sign up to set email alerts
|

Neuron dynamics on directional surfaces

Abstract: We quantify neuronal growth on substrates with controlled geometries and present a theoretical approach that describes the motion of axons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…Treatment of neural cells with blebbistatin results in extensive outgrowth of neurites as a consequence of abolished retrograde actin flow, when the balance of extension and retraction of cell protrusion is shifted to extension. Several studies employed blebbistatin to demonstrate the role of actomyosin contractility using primary neurons from mice (Kollins et al, 2009;Hur et al, 2011;Yu et al, 2012;Dupraz et al, 2019;, rats (Allingham et al, 2005;Kubo et al, 2008;Kollins et al, 2009;Pool et al, 2011;Roland et al, 2014;Spedden et al, 2014;Evans et al, 2017;Wang et al, 2017Wang et al, , 2020Tanaka et al, 2018;Basso et al, 2019;, chickens (Rosner et al, 2007;Kollins et al, 2009;Xie et al, 2014), or even gastropods, such as Aplysia (Medeiros et al, 2006) and Helisoma trivolvis (Tornieri et al, 2006). These studies were performed in non-human primary neural cells, and investigated the neurite growth in matured neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of neural cells with blebbistatin results in extensive outgrowth of neurites as a consequence of abolished retrograde actin flow, when the balance of extension and retraction of cell protrusion is shifted to extension. Several studies employed blebbistatin to demonstrate the role of actomyosin contractility using primary neurons from mice (Kollins et al, 2009;Hur et al, 2011;Yu et al, 2012;Dupraz et al, 2019;, rats (Allingham et al, 2005;Kubo et al, 2008;Kollins et al, 2009;Pool et al, 2011;Roland et al, 2014;Spedden et al, 2014;Evans et al, 2017;Wang et al, 2017Wang et al, , 2020Tanaka et al, 2018;Basso et al, 2019;, chickens (Rosner et al, 2007;Kollins et al, 2009;Xie et al, 2014), or even gastropods, such as Aplysia (Medeiros et al, 2006) and Helisoma trivolvis (Tornieri et al, 2006). These studies were performed in non-human primary neural cells, and investigated the neurite growth in matured neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A major determinant of the reduced neuronal regeneration is the diminished axonal growth capacity of mature neurons. Extensive studies have been performed to elucidate the process of axonal growth impairment (Allingham et al, 2005;Medeiros et al, 2006;Tornieri et al, 2006;Rosner et al, 2007;Kubo et al, 2008;Kollins et al, 2009;Hur et al, 2011;Pool et al, 2011;Yu et al, 2012;Roland et al, 2014;Spedden et al, 2014;Xie et al, 2014;Evans et al, 2017;Wang et al, 2017Wang et al, , 2020Tanaka et al, 2018;Basso et al, 2019;Dupraz et al, 2019;, and, in addition to the intrinsic factors, revealed the importance of environmental inhibitory mechanisms in retarded axonal growth (Ichikawa et al, 2009;Hur et al, 2011;Tan et al, 2011;Beller and Snow, 2014;Baldwin and Giger, 2015;Nakamura et al, 2019). Because of the limited availability of human neural tissues, most of these studies used rodent or avian models.…”
Section: Introductionmentioning
confidence: 99%
“…Each surface is characterized by a different value of the pattern spatial period d , defined as the distance between two neighboring ridges ( Figure 1 a). To make these periodic patterns, we used a simple fabrication method based on imprinting diffraction grids with different grating constants onto PDMS substrates ( Supplementary Materials and [ 33 ]). The direction of the pattern is shown in Figure 1 by the parallel bright stripes (ridges) and by the parallel dark stripes (troughs).…”
Section: Methodsmentioning
confidence: 99%
“…All neuronal cells have been imaged using fluorescence microscopy (a total of 18 images). Fluorescence images were acquired using a standard Fluorescein isothiocyanate -FITC filter: excitation: 495 nm and emission: 521 nm (details on acquiring the fluorescence images are provided in the Supplementary Materials and [ 33 ]). For the experiments on chemically modified cells, we have treated the neurons with either: (1) Taxol (10 μM concentration) or (2) the chemical compound Y-27632 (10 μM concentration), which have been added to the neuron growth medium at the time of plating ( Supplementary Materials ).…”
Section: Methodsmentioning
confidence: 99%
“…While these works discuss mechanisms and constraints at play in chemotaxis or mechanical guidance, they do not seek to describe the path of the growth cone as a response to these stimuli. To that end, trajectories of growth cones seen as a random motion on a 2D substrate have been studied by multiple authors (Katz et al 1984;Mortimer et al 2010;Maskery et al 2004;Van Ooyen 1999, 2000;Krottje and Van Ooyen 2007;Borisyuk et al 2008;Buettner et al 1994;Wang et al 2003;Pearson et al 2011;Ben-Jacob 2000, 2001;Basso et al 2019;Yurchenko et al 2019Yurchenko et al , 2021Davis et al 2017;Roberts et al 2014); see also the review by Maskery and Shinbrot (2005). The main focus in these works is not the mechanism of elongation, as treated before, but rather the shape and statistical properties of growth cone trajectories, as a function of external cues.…”
Section: Guidancementioning
confidence: 99%